Enrofloxacin and ciprofloxacin residues in broiler chicken feathers after enrofloxacin oral administration - Marchetti, Maria Laura (2019)
Antibiotics in animal feed are a public health concern. Drug residues could eventually be detected in animal food products intended for human consumption. Our aim was to study the residue depletion of enrofloxacin and its metabolite ciprofloxacin in broiler chicken feathers. A validated HPLC-fluorescence method was used to quantify both compounds in feather samples. Broiler chickens were treated through drinking water with 10 mg Kg-1 d of enrofloxacin for 5 consecutive days. Feather samples were taken from 10 random birds per day until 9 days. Extraction was performed by a liquid/liquid technique. Both fluoroquinolones concentrations were determined by liquid chromatography with fluorescence detection. High levels of enrofloxacin and ciprofloxacin were found in feathers after oral administration and these compounds were detected for 9 days. Feather meal is a potential source of drug residues that can pass through the food chain when contaminated meal is fed to food-producing animals. In the present study enrofloxacin and ciprofloxacin concentrations were 0.20 to 5.46 µg g-1 between 1 to 9 days after final treatment, which means that withdrawal time fit for edible tissues is not adequate to reduce antimicrobial residues in chicken feathers. Further studies to establish a withdrawal time may be useful to avoid that drug residues could result in adverse health consequences like increase in antibiotic resistance.